1993
DOI: 10.1002/1520-6696(199301)29:1<29::aid-jhbs2300290105>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Social control doctrines of mental illness and the medical profession in nineteenth-century America

Abstract: Social control doctrines of mental disorders have influenced a generation of psychologists and have shaped attitudes and discussions about how to treat the mentally ill. In light of the failure of deinstitutionalization as a public policy and the contemporary concern with the medical or biological bases of psychiatric disorders, this paper re‐examines social control doctrines. Reviewing mid‐nineteenth century statistical accounts, the author challenges claims of social control theorists and shows that in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Though destigmatization efforts began early in the 18 th century1, the view that mental illness is a character problem has persisted. A 2000 study demonstrated that attitudes of British adults toward those with mental illness remain quite negative2.…”
Section: Attitudes Of College Students Toward Mental Illness Stigma Amentioning
confidence: 99%
“…Though destigmatization efforts began early in the 18 th century1, the view that mental illness is a character problem has persisted. A 2000 study demonstrated that attitudes of British adults toward those with mental illness remain quite negative2.…”
Section: Attitudes Of College Students Toward Mental Illness Stigma Amentioning
confidence: 99%